Effects of arousal modulation via resonance breathing on craving and affect in women with substance use disorder. (April 2022) - Price, Julianne L.; Bates, Marsha E.; Morgano, Julie; Todaro, Sabrina; Uhouse, Sarah Grace; Vaschillo, Evgeny; Vaschillo, Bronya; Pawlak, Anthony; Buckman, Jennifer F.
Highlights: A paced breathing app was tested as an adjunct to addiction treatment-as-usual. Group randomization paced the breath to 0.1 Hz (resonance) or ∼ 0.23 Hz (sham) Women in the sham condition showed an increase in craving during treatment. Women in the resonance condition showed no change in craving. Just-in-time resonance breathing blocks increased craving seen in the sham condition. Abstract: Background: Craving for alcohol and other drugs is a complex in-the-moment experience that involves within-person changes in physiological arousal and affect. We evaluated the utility of a just-in-time, self-administered resonance breathing smartphone application (app) to reduce craving and improve affect in women during outpatient treatment for substance use disorders (SUD). Methods: Women (N = 57) receiving outpatient addiction treatment were randomized to practice either cardiovascular resonance breathing (0.1 Hz/6 breaths per minute) or a sham (∼0.23 Hz/14 breaths per minute) in the face of urges over an 8-week intervention. Craving (Penn Alcohol Craving Scale) and affect (Positive and Negative Affect Scale) were collected weekly throughout the intervention. App data were uploaded weekly to assess frequency of use. Generalized Estimated Equations modeled craving and affect as a function of group randomization and app use frequency across the 8-week intervention. Findings: Higher levels of craving were associated with more frequent app use. The group X app use interaction was significant for craving. Frequent app use during the intervention phase was associated with lower craving levels in the resonance breathing group relative to the sham group over the 8-week intervention. There was no effect of app use frequency on affect measures. Conclusions: Women assigned to practice sham breathing who used the intervention frequently experienced elevations in craving that are commonly reported during outpatient SUD treatment. Women assigned to resonance breathing who used the intervention frequently did not experience such increases. Resonance breathing may be protective against triggers in outpatient treatment. Physiological mechanisms are discussed.